Association between CORIN promoter methylation and stroke: Results from two independent samples of Chinese adults - Chen, Linan; Jiang, Jun; Yao, Jialing; Lu, Ying; Zhang, Xiaolong; Zhang, Mingzhi; Zhang, Qiu; Peng, Hao (Frontiers in Neurology, 2023)
Objective As the physical activator of natriuretic peptides, corin has been associated with stroke, but the underlying mechanism is not very clear. Here, we examined whether the CORIN promoter’s methylation, an epigenetic DNA modification, was associated with the risk of stroke in two independent samples. Methods A total of 1771 participants including 853 stroke cases and 918 healthy controls were included as a discovery sample and 2,498 community members with 10 years of follow-up were included as a replication sample. DNA methylation of the CORIN promoter was quantified by target bisulfite sequencing in both samples. We first examined the single CpG association, followed by a gene-based analysis of the joint association between multiple CpG methylation and stroke, adjusting for conventional risk factors. Results The single CpG association analysis found that hypermethylation at all of the 9 CpG sites assayed was significantly associated with lower odds of prevalent stroke in the discovery sample (all p < 0.05), and three of them located at Chr4:47840038 (HR = 0.74, p = 0.015), Chr4:47839941 (HR = 0.80, p = 0.047), and Chr4:47839933 (HR = 0.82, p = 0.050) were also significantly associated with incident stroke in the replication sample. The gene-based association analysis found that DNA methylation of the 9 CpG sites at the CORIN promoter was jointly associated with stroke in both samples (all p < 0.05). Conclusion DNA methylation levels of the CORIN gene promoter were lower in stroke patients and predicted a higher risk of incident stroke in Chinese adults. The underlying causality warranted further investigation.